The Revolution of Islamic Character in English as a Foreign Language (EFL) Learning for Millennial Muslim Generation - Naily Inayatul Maghfirah; Irfan Masrur; Zulfa Kamilatun Nafilah (proceedings.icesy, 2026)
The purpose of this study is to examine the integration of Islamic values into English as a Foreign Language (EFL) teaching methods and to analyze students’ motivation and attitudes toward learning English. This study employs a qualitative approach, with data collected through interviews, classroom observations, and document analysis. The findings reveal that the implementation of Islamic character values, including honesty, discipline, responsibility, tolerance, and social awareness, not only enhances students’ language proficiency but also strengthens their moral identity. Students who internalize these values in EFL learning demonstrate higher motivation and more positive attitudes toward English. The development of Islamic character in EFL learning for the millennial Muslim generation reflects increasing need to integrate moral, spiritual, and cultural dimensions into modern education. By incorporating Islamic content, contextual learning materials, and value-based pedagogical strategies, EFL instruction becomes more meaningful and relevant to learners’ identities in a globalized context. Overall, the integration of Islamic character education in EFL classrooms contributes to improved motivation, ethical awareness, and intercultural competence while preserving students’ religious and moral values.